Dr. Andries Albertus Odendaal Snr., evangeliedraer in 'n multi-dimensionele konteks. 'n Kort historiese oorsig en sendingkundige evaluering van sy lewe en werk (Deel 2) - P. Robinson (Acta Theologica)
This is the second of two articles which briefly introduce the life and work of a so-called “local missionary” of the Dutch Reformed Church in South Africa. This second part of the article discusses Odendaal’s involvement in theological and pastoral training, as well as his continued contributions on synodical level, in particular his endeavour for church unity, his appreciation of and working in the vernacular, his appointment as Bible translator, his passion for preaching the gospel, a testing experience in his life, and the way in which he was honoured by old students and the University of the Free State. The article concludes with a short missiological assessment of Odendaal’s life and work.